Education on Transmission Patterns of Parasitic Infections by Nurses - Reqgi First Trasia (Genius Journal, 2021)
Introduction: Disease caused by helminth, protozoa, arthropods, and fungi was still a problem in the world. These parasitic diseases were classified as neglected tropical disease. Nurses play a significant role in the education on transmission patterns of helminth infections. However, the role of nurses in the education on transmission patterns of protozoa infections was still not well known and discussed. Objective: The aim of this article is to review the role of nurses in the education on transmission patterns of parasitic infection. Method: Writing a study of this scientific articles is made using the reading method model or literacy, analyzing and tracing various references. Result: This review found that nursing professional staff has a significant contribution in the education on transmission patterns of parasitic infection. Conclusion: Every nurse must know how to give the best contribution in each case of parasitic disease, especially helminth, protozoa, arthropods, and fungal infection which is cosmopolite.